2020
DOI: 10.24843/ujossh.2020.v04.i02.p08
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Slang Words in Song Lyrics Used in the Songs “That’s What I Like”, “Smoke On The Water”, and “Ch-Check It Out”

Abstract: The paper entitled “An Analysis of Slang Words in Song Lyrics Used in the Songs “That’s What I Like”, “Smoke On The Water”, and “Ch-Check It Out”. This study concern with the analysis of slang words in the Songs “That’s What I Like”, “Smoke On The Water”, and “Ch-Check It Out”. There are three statement problems (1) What are the types of slang words used in the song? (2) What is the meaning of slang words in the three sample that are in the lyric? (3) What is dominant type of slang words of three song lyrics? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The findings show that there are six kinds of process creating slang words such as, etymology, coinage, compounding, blending, clipping, and acronyms. The fourth is "An Analysis of Slang Words in Song Lyrics Used in the Songs "That's What I Like", "Smoke On The Water", and "Ch-Check It Out", this study was written by Karmila and Ayu (2020). Which aims to determine the type of slang words, the meaning of slang, and the dominant type of slang words in song lyrics.…”
Section: Introductionmentioning
confidence: 99%

Primary Slangs Occurred on Greyson Chance’s Selected Songs

Purnamasari,
I Dewa Ayu Devi Maharani Santika,
Komang Dian Puspita Chandra
2022
elysian
“…The findings show that there are six kinds of process creating slang words such as, etymology, coinage, compounding, blending, clipping, and acronyms. The fourth is "An Analysis of Slang Words in Song Lyrics Used in the Songs "That's What I Like", "Smoke On The Water", and "Ch-Check It Out", this study was written by Karmila and Ayu (2020). Which aims to determine the type of slang words, the meaning of slang, and the dominant type of slang words in song lyrics.…”
Section: Introductionmentioning
confidence: 99%

Primary Slangs Occurred on Greyson Chance’s Selected Songs

Purnamasari,
I Dewa Ayu Devi Maharani Santika,
Komang Dian Puspita Chandra
2022
elysian
“…The slang word is one of an interesting study to be analyzed. Dewi and Widiastuti (2020), in their research analysed slang words found in song lyrics. They used the theory by Patridge (2004: 204) to find out the types of slang words and to analyze the meanings of slang words used theory by Leech (1974).…”
Section: Introductionmentioning
confidence: 99%